Show that for any z C an Z not equal to 1 one has 1 + z +...+z^n = (1-z^(n+1))/(1-z) and use it to show that 1 + from k=1 to n of cos(k ) = 1/2 + (sin((2n+1) /2))/(2sin( /2))
Follow Math Help Forum on Facebook and Google+
Originally Posted by LCopper2010 Show that for any z C an Z not equal to 1 one has 1 + z +...+z^n = (1-z^(n+1))/(1-z) and use it to show that 1 + from k=1 to n of cos(k ) = 1/2 + (sin((2n+1) /2))/(2sin( /2)) Now multiply the numerator and denominaotor by to get Now just equate the real and immaginary parts to get your result
View Tag Cloud